Repetition markers in junior high school students’ essays - Abdul Wahid; Andis Syukri Syamsuri; Abdan Syakur (Universitas Islam Sultan Agung, 2022)
Repetition plays an important role in an essay because it functions to connect one proposition to another in an essay. However, junior high school students as writers are still often found using repetition markers that do not show a clear function as a means of affirmation and their appearance in student essays tend to be boring for readers. This study aims to identify and explore the form of using repetition as a marker of propositional relations in junior high school students' essays. This research uses a qualitative approach and is categorized into the type of discourse analysis research. This study involved 94 eighth grade students of SMP Negeri 1 Balikpapan as research subjects. The data in this study were collected using a technique as proposed by (Sudaryanto, 2015), namely the simak-catat technique and interview technique. The data analysis of this research consisted of three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are three types of repetition that are utilized as a means to link one proposition to another in the research subject's essay, namely exactly the same repetition, repetition with shapeshifting, and repetition with a partial disappearance. Among the three categories, exactly the same repetition is dominantly used so that it becomes the hallmark of the research subject's essay. The repetition of elements of the proposition that is repeated is also found in the essay of the research subject, causing boredom or redundancy. The findings of this study have an important contribution for teachers and education practitioners to optimize the literacy culture and students' critical thinking so that they are skilled in using repetition as a marker of propositional relations in written language.